2019
DOI: 10.1016/j.seizure.2019.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family perspectives of paediatric psychogenic non-epileptic seizures: A systematic review

Abstract: Exploring the perspectives of those affected by psychogenic non-epileptic seizures (PNES) may be essential in learning more about the nature of this condition. The aim of this systematic review is to synthesise the evidence regarding the perspectives of children and adolescents with PNES, and the perspectives of their parents, caregivers and families. Studies were included if they (1) explored PNES in a paediatric population, (2) explored the perspectives of the child or adolescent with PNES, or the perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…This communication is often sufficient to reassure children and to improve the clinical picture, especially in subjects with acute onset. Importantly, information about the FND diagnosis should be shared with teachers, educators and acquaintances who have everyday contacts with the patient, to prevent them from believing that these symptoms are fabricated or under the child’s control, and ultimately to prevent the child from developing the automatic conviction of not being believed when reporting them (Dunne et al, 2019). If the clinician suspects that the diagnosis is not fully understood and accepted by the family or the child, it is suggested to conduct follow-up interviews until all doubts are resolved (Benbadis and Allen, 2004; Grattan-Smith and Dale, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This communication is often sufficient to reassure children and to improve the clinical picture, especially in subjects with acute onset. Importantly, information about the FND diagnosis should be shared with teachers, educators and acquaintances who have everyday contacts with the patient, to prevent them from believing that these symptoms are fabricated or under the child’s control, and ultimately to prevent the child from developing the automatic conviction of not being believed when reporting them (Dunne et al, 2019). If the clinician suspects that the diagnosis is not fully understood and accepted by the family or the child, it is suggested to conduct follow-up interviews until all doubts are resolved (Benbadis and Allen, 2004; Grattan-Smith and Dale, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…After answering 10 questions, a total score of 1 to 10 indicated low-quality research, 11 to 20 indicated medium-quality research, and 21 to 30 indicated highquality research. 31 Two of the studies included in this review were single-group pretest and posttest studies. Therefore, the Joanna Briggs Institute Critical Appraisal Checklist 32 for Quasi-Experimental Studies (nonrandomized experimental studies) was used.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this disruption to daily life was described in present findings, it seemed more closely linked to a desire to be taken seriously given the disruption caused. Young people and children with functional seizures have too described being understood and taken seriously as most helpful in moving forward [37] and receiving this understanding and reassurance from healthcare professionals (HCPs) in particular has been noted in both current and previous findings [31]. Present patients explained that the terms utilised by HCPs played a role in feeling taken seriously, with the less offensive terms ('NEAD', 'FNEA', 'functional seizures') generally being favoured in this regard, although some criticised the use of "non-epileptic" as offensive.…”
Section: Shared Understandingmentioning
confidence: 99%
“…Many described frustration at feeling "palmed off" and that doctors made them feel they were "wasting their time". Negative experiences with HCPs are frequently reported [36], such as questions around the validity of the condition [39], and accusations of the patient being in control of the seizures [37] or attention seeking [13]. Terminology plays a significant role in this; 'pseudoseizures' and 'hysteria' were overwhelmingly disliked presently due to the implied accusation of "faking it".…”
Section: Feeling Alonementioning
confidence: 99%